The Effect of Social Media Use Intensity and Locus of Control on Entrepreneurial Intentions among Phase F Students at SMK Negeri 5 Padang - Eventina Eventina; Dessyta Gumanti; Detman Detman (The Future of Education Journal, 2026)
This study aims to examine the influence of social media usage intensity and locus of control on the entrepreneurial interest of Phase F students at SMK Negeri 5 Padang. The research employed a quantitative associative approach. The population consisted of 403 Grade XI Phase F students, while 201 respondents were selected using the Slovin formula and purposive random sampling technique. Data were collected using validated and reliable questionnaires. Data analysis included descriptive statistics, prerequisite tests, multiple linear regression, partial hypothesis testing (t-test), simultaneous hypothesis testing (F-test), and coefficient of determination (R²) using SPSS version 25. The findings indicate that social media usage intensity has a positive and significant effect on students’ entrepreneurial interest (t = 9.455; p < 0.05). Likewise, locus of control has a positive and significant effect on entrepreneurial interest (t = 5.882; p < 0.05). Simultaneously, both independent variables significantly influence entrepreneurial interest (F = 427.188; p < 0.05). The coefficient of determination indicates that 73.20% of the variance in entrepreneurial interest is explained by social media usage intensity and locus of control, while the remaining 26.80% is explained by other variables outside the scope of this study. These findings imply that productive use of social media and strengthening students' internal locus of control can enhance entrepreneurial interest among vocational high school students.